Design of High Speed Low Power Multiplier Using Reversible Logic A Vedic Mathematical Approach - Gopi Krishna, P; Subrahmanyam, KV; Chandra Sekhar, S (International Journal of Computer Sciences and Engineering, 2014)
Reversibility plays a fundamental role when computations with minimal energy dissipation are considered. In recent years, reversible logic has emerged as one of the most important approaches for power optimization with its application in low power CMOS, optical information processing, quantum computing and nanotechnology. This research proposes a new implementation of adder in reversible logic. The design reduces the number of gate operations compared to the existing adder reversible logic implementations. So, this design gives rise to an implementation with a reduced area and delay. We can use it to construct more complex systems in nanotechnology.